Trazabilidad en la cadena de suministros en la cooperativa de producción pesquera artesanal odisea, para mejorar su competitividad - Alvarado Félix, Angelo Antonio (2023)
In an increasingly competitive business environment geared towards quality and transparency, traceability in the supply chain has emerged as an essential tool to improve operational efficiency and customer confidence. This thesis focuses on the Artisanal Fishing Cooperative Odyssey and its quest to improve its competitiveness through the improvement of the supply chain and the identification of areas of optimization that result in failures in the delivery management system of the products. The lack of a system to know the origin of the products has generated instability in the processes, affecting the quality and reliability of the products delivered. To address these shortcomings, it is proposed to implement a traceability system to track products at all stages of the supply chain. This will provide a comprehensive view of the processes and allow precise identification of the improvement points. Through the implementation of this traceability system, it is expected to improve operational efficiency, reduce delivery times, and increase customer confidence by providing transparent information about product origin and quality. This research seeks to